Vacuolar signaling, biogenesis, and quality control in plants - Julian, Jose; Dagdas, Yasin (Current opinion in plant biology, 2025)
The plant vacuole, traditionally viewed as a static storage organelle, has recently emerged as a dynamic hub orchestrating signaling, metabolic integration, and stress responses. This review synthesizes recent advances that position the vacuole as a pivotal regulator of plant development and environmental adaptation. We discuss the vacuole's multifaceted roles in ion sequestration, lipid trafficking, mechanosensing, and signal transduction, highlighting its central role in preserving cellular homeostasis. We summarize recent data supporting two distinct forms of vacuolar biogenesis: inheritance from existing organelles and de novo formation. Lastly, we discuss our recent findings that define a vacuolar quality control (VQC) pathway, safeguarding tonoplast integrity during stress. Collectively, these insights redefine our understanding of the vacuole's essential contributions to plant physiology and resilience, advocating for an updated conceptual framework that recognizes the vacuole as a central hub for developmental processes and environmental adaptation.